Islam in modern Malay literature: examining the role and position of “story” according to Persuratan Baru - Abdul Rani, Mohd. Zariat; Ismail, Muhd. Zulkifli (International Islamic University Malaysia, 2023)
This article discusses the synchronisation of Persuratan Baru’s idea on the role and position of stories in literature to Islam. Persuratan Baru (PB) is a literary notion proposed by Mohd. Affandi Hassan as an alternative to resolve the confusion of knowledge in modern Malay literature. To this end, PB upholds Islam particularly its core doctrine Tawhid as its conceptual framework which recognises the Qur’an and Prophetic Sunnah as legitimate sources of knowledge. Among the major ideas of PB is “Ilmu-Cerita” (Knowledge-Story) which prioritises “Ilmu” (Knowledge) and subordinates “Cerita” (Story) to “Ilmu.” More important is Affandi Hassan’s statement that his idea of “Ilmu-Cerita” is indeed Islamic as it is inspired by the Qur’an. No critical research has examined the synchronisation of PB idea and “Ilmu-Cerita” to Islam. This article is structured to achieve two objectives. Firstly, to discuss PB’s idea on “Ilmu-Cerita” as expounded by Affandi Hassan in his writings. Secondly, to examine the synchronisation of the idea to Islam by referring to authoritative (mu’tabar) Arabic commentaries of the Qur’an. This study applies a textual analysis approach that outlines two levels of reading procedure, i.e., descriptive reading and analytical reading. The study reveals that in PB’s perspective the aim of literary writing is to convey ilmu (knowledge), and therefore cerita (story) functions as a tool in conveying knowledge. Close reading on the mu’tabar Arabic commentaries of the Qur’an reveals that stories in the Qur’an seek to convey knowledge, i.e., good lessons that benefit mankind in everyday life. In this context that stories in the Islamic perspective serve as a tool to convey knowledge. With this understanding, PB’s idea of “Knowledge-Story” is found in synchronisation with the teaching of Islam.